GEOLOGICAL CONDITIONS OF HARZ MAGMATIC COMPLEX: (Federal Republic of Germany) (Proceedings of the YSU C: Geological and Geographical Sciences, 2008)
The Harz massif is located in the northern part of the area of Germany. The Harz rocks compose geologically hard, horst, strongly metamorphized upper-paleozoic complex with mainly developed Devon and lower-carbon formations. Plutonic formations like harzburgite-gabbro and banatite-granitoide formation to which are related the massifs Harburg, Broken, Ramberg, Oker and Bode dyke are typical for Harz.
Keywords: Harz; Germany; banatite-granitoide formation; harzburgite-gabbro formation; Harburg, Broken, Ramberg, Oker and Bode dyke